LANDMARK “MONUMEN YOGYA KEMBALI” STUDI MOTIVASI, PENGAMBILAN KEPUTUSAN, DAN KEPUASAN PENGUNJUNG - Ganes Satya Aji (JURNAL TATA KELOLA SENI, 2015)
This research tries to identify factors, factor interpretation, and relationship of thevisitor behavior on landmarks Yogya Kembali Monument (Monjali) in Yogyakarta.Visitor behavior has three dimensions: Motivation, Decision-making, and Satisfaction.Using200respondentwhocollectfromJudmentalSamplingMethodandana-lyzed by Factor Analysis and Arithmetic Mean Test with a quantitative approach. From the analysis conducted to show that the perception of visitors is relatively highso that the motivation to visit because of the learning and aesthetic factors, artisticattraction factors, and recreational factors. Visitor considering, first is facilities andinfrastructure factors, benefits visit factors, and characteristics of visitors and tripsoverview factors to decide to visit. After the visit, visitors were satisfied because ofthe quality of service factors and physical environmental factors given from Monjalimonument. Then the hypothesis tested results indicate that there is a strong enough relationship between the factors that form of variable motivation, decision variab-les, and variable visitor satisfaction.